Existence of positive solutions to an arbitrary order fractional differential equation via a mixed monotone operator method - Jleli, Mohamed; Samet, Bessem (Nonlinear Analysis: Modelling and Control, 2015)
In this paper, using a mixed monotone operator method, we study the existence and uniqueness of positive solutions to a nonlinear arbitrary order fractional differential equation. An example is provided to illustrate the main result.
Keywords: fractional differential equation; positive solution; cone; mixed monotone